Modern approaches to teaching a foreign language at agricultural higher education institution - Stukalo, Olena; Стукало, Олена Анатоліївна (Класичний приватний університет, 2022)
The article analyzes modern approaches to teaching foreign languages and substantiates the feasibility of their use in agricultural institutions of higher education. Methods of teaching foreign languages are constantly evolving and are in search of the most effective ways of learning. Modernization of education in agricultural higher education institutions requires a wide range of research and development related to the introduction of the latest technologies and modern approaches in the educational process. Graduates of agricultural higher education institutions must speak a foreign language at a level sufficient for professional communication, and for this purpose it is necessary to ensure the effectiveness of training and improve the quality of acquired knowledge, skills and abilities. У статті проаналізовано сучасні підходи до викладання іноземної мови й обґрунтовано доцільність їх використання в аграрних закладах вищої освіти. Методика викладання іноземних мов постійно розвивається та перебуває у пошуку найефективніших способів навчання. Модернізація освіти в аграрних закладах вищої освіти потребує проведення широкого кола наукових досліджень і розробок, пов’язаних із впровадженням у навчальний процес новітніх технологій та сучасних підходів. Випускники аграрних закладів вищої освіти повинні володіти іноземною мовою на достатньому для професійного спілкування рівні, а для цього треба забезпечити ефективність навчання та покращити якість отриманих знань, навичок та вмінь.
Сучасні підходи до навчання іноземної мови в аграрних закладах вищої освіти
Keywords: foreign language; іноземна мова; approach; підхід; means of communication; засоби спілкування; professional purpose; професійна ціль; teaching method; метод навчання